Latent semantic indexing using eigenvalue analysis for efficient information retrieval - Aswani Kumar, Cherukuri; Srinivas, Suripeddi (Zielona Góra: Uniwersytet Zielonogórski)
Text retrieval using Latent Semantic Indexing (LSI) with truncated Singular Value Decomposition (SVD) has been intensively studied in recent years. However, the expensive complexity involved in computing truncated SVD constitutes a major drawback of the LSI method. In this paper, we demonstrate how matrix rank approximation can influence the effectiveness of information retrieval systems.
Keywords: information retrieval; latent semantic indexing; eigenvalues; rank reduction; Singular Value Decomposition (SVD)